Experimental analysis of tubular wall-threaded sections submitted to ultra-low cycling fatigue (Gaceta Técnica, 2017)
The present work of investigation studies the behavior of steel structural sections of thin wall, made in Venezuelan Conduven ECO, of square cross section, constructed in the form of a cantilever type beam, under the effects of fatigue of ultra-low cycling. Experimental tests were carried out applying histories of cyclic displacements, with low speed and acting in a range that goes from the yielding effort to the last effort of the element, obtaining a degradation of the resistant capacity of the elements through the phenomenon of fatigue of ultra-low Cycling, induced by the appearance of the fault by local buckling in the elements tested.
Keywords: fatigue of ultra-low cycling; tubular steel elements; failure due to local buckling